2012
DOI: 10.4236/psych.2012.329113
|View full text |Cite
|
Sign up to set email alerts
|

Grade Retention and Seventh-Grade Depression Symptoms in the Course of School Dropout among High-Risk Adolescents

Abstract: The relationship between grade retention and adolescent depression in the course of school dropout is poorly understood. Improving knowledge of the mechanisms involving these variables would shed light on at-risk youth development. This study examines whether depression in adolescence moderates the relationship between grade retention and school dropout in a high-risk sample. Seventh-grade students (n = 453) from two low-SES secondary schools in Montreal (Quebec, Canada) were followed from 2000 to 2006. Self-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 54 publications
(78 reference statements)
1
13
0
7
Order By: Relevance
“…Considering academic achievement as an endogenous variable, Fletcher assumed that the total effect of depression on educational attainment may be reduced as part of the effect operated through decreases in the GPA [ 57 ]. The reciprocal effect of academic achievement and depressive symptoms had also been noted by Quiroga [ 32 ] who observed that youth combing a history of grade repetition and depression were most at risk to drop out of high school [ 32 ]. As studies including academic confounders had very different foci varying from grade repetitions [ 5 , 26 , 32 ], school characteristics [ 50 , 51 ], attitudes [ 63 ] and grades or test scores as a proxy for academic performance [ 10 , 15 , 52 , 54 , 57 ], a direct comparison of results was difficult.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Considering academic achievement as an endogenous variable, Fletcher assumed that the total effect of depression on educational attainment may be reduced as part of the effect operated through decreases in the GPA [ 57 ]. The reciprocal effect of academic achievement and depressive symptoms had also been noted by Quiroga [ 32 ] who observed that youth combing a history of grade repetition and depression were most at risk to drop out of high school [ 32 ]. As studies including academic confounders had very different foci varying from grade repetitions [ 5 , 26 , 32 ], school characteristics [ 50 , 51 ], attitudes [ 63 ] and grades or test scores as a proxy for academic performance [ 10 , 15 , 52 , 54 , 57 ], a direct comparison of results was difficult.…”
Section: Resultsmentioning
confidence: 71%
“…Internalizing disorders refer to anxiety and mood disorders, both associated with educational attainment [ 5 , 32 , 33 , 40 , 56 - 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qurioga et al reported that depression increased the risk of students dropping out of school by 2.75-fold. 30 Thus, we may have under-sampled depressed students in this study. In addition, depressed students who are bullied at school may be more likely to withdraw from school than perpetrators and neutrals who are not involved regularly in bullying.…”
Section: Discussionmentioning
confidence: 99%
“…There is a worldwide need for early intervention of clinically diagnosable mental health concerns in children [15]. Previous studies reveal that unaddressed mental health problems among children and adolescents can result in lower educational achievement and poor physical and social outcomes [16,17] The following diagram describes the behavioral health workfl ow:…”
Section: Resultsmentioning
confidence: 99%